Adabī kālam - Mīrzā Adīb (Pākistān Buks aind́ Lit́rerī Saʾund́z, 1991)
Critical appreciation of the works of noted Urdu writers; articles, previously published in the Urdu daily Navā-yi vaqt, Lahore
In arab. Schrift, Urdu
Keywords: Aufsatzsammlung